2014
DOI: 10.1007/s00586-013-3163-0
|View full text |Cite
|
Sign up to set email alerts
|

Early experience of MAGEC magnetic growing rods in the treatment of early onset scoliosis

Abstract: Purpose Magnetically controlled growing rod systems have been introduced over recent years as an alternative to traditional growing rods for management of early onset scoliosis. The purpose of this paper is to report our early experience of a magnetically controlled growing rod system (MAGEC, Ellipse). Methods Review of pre-operative, postoperative and follow-up Cobb angles and spinal growth in case series of eight patients with a minimum 23 months' follow-up (23-36 months). Results A total of six patients had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
84
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(90 citation statements)
references
References 17 publications
5
84
0
Order By: Relevance
“…Preliminary studies of MCGRs have been met with optimism with respect to achieving the same results of TGRs. [34][35][36] Dannawi et al 34 demonstrated that the mean coronal Cobb angle improved from 69° to 41° after MCGRs with a mean of 4.8 distractions per patient were used over 15 months. The T1 to S1 length increased a mean of 3.5 cm during this time period.…”
Section: Mcgrmentioning
confidence: 99%
“…Preliminary studies of MCGRs have been met with optimism with respect to achieving the same results of TGRs. [34][35][36] Dannawi et al 34 demonstrated that the mean coronal Cobb angle improved from 69° to 41° after MCGRs with a mean of 4.8 distractions per patient were used over 15 months. The T1 to S1 length increased a mean of 3.5 cm during this time period.…”
Section: Mcgrmentioning
confidence: 99%
“…MCGRs are gaining in popularity among patients and surgeons as they are the least invasive technique for patients with a high degree scoliosis [6][7][8][9][10][11], both for primary operations and conversion cases from the traditional growing rods [12]. Once implanted (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1), MCGRs are elongated non-invasively every 3 months using an external remote controller (the external magnet) in an outpatients' clinic, while the patient is conscious. The lengthening procedure lasts approximately 40 s per rod and the total length is measured using a plain radiograph [8]. Recent studies have also investigated the reliability of other imaging modalities, including ultrasound [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…These new rods seem to provide distraction of the spine with no need for repeated lengthening surgeries before definitive fusion [5][6][7]. Therefore, we have applied this distraction technique in adult patients to obtain gradual lengthening of the spine by posterior access alone, thus avoiding the anterior access and vertebrectomy related risks, as well as halo-traction discomfort.…”
Section: Introductionmentioning
confidence: 99%